The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.vaccine.2017.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Post-marketing safety surveillance for inactivated and live-attenuated Japanese encephalitis vaccines in China, 2008–2013

Abstract: While our analysis did not find apparent safety concern of JE vaccines in China, further study should consider JE-I vaccines and febrile convulsion, and taking more sensitive methods to detect signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The live-attenuated vaccine is immunogenic, induces long term immunity, and requires one or two doses in childhood [143]. In China and Nepal, two dose regimens in children led to seroconversion in 97.5% and 98% of recipients, respectively, with high levels of antibody persisting for up to five years following immunisation [144,145]. While initially only available in China, it is now the recommended vaccine for many endemic countries in Asia [146].…”
Section: Jev Vaccinationmentioning
confidence: 99%
“…The live-attenuated vaccine is immunogenic, induces long term immunity, and requires one or two doses in childhood [143]. In China and Nepal, two dose regimens in children led to seroconversion in 97.5% and 98% of recipients, respectively, with high levels of antibody persisting for up to five years following immunisation [144,145]. While initially only available in China, it is now the recommended vaccine for many endemic countries in Asia [146].…”
Section: Jev Vaccinationmentioning
confidence: 99%
“…Safety data from clinical trials showed SA14-14-2 JE vaccine to be well-tolerated and established the vaccine’s good safety profile [ 3 , 6 , 7 , 10 , 18 ]. Available post-marketing surveillance data primarily have been collected through routine passive AEFI surveillance systems and during the vaccine’s use in routine immunization programs [ 19 21 ]. It is difficult to compare AEFI rates from post-marketing surveillance conducted in diverse settings with different methodologies, and when SA14-14-2 JE vaccine is used in routine immunization programs when it is often co-administered with measles or other vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…It may be composed of entire virions or bacterial cells or only their fragments. Inactivated virus vaccines that are currently used include the inactivated polio vaccine [ 201 ], inactivated Japanese encephalitis vaccine [ 202 ], inactivated hepatitis A vaccine [ 203 ], inactivated rabies vaccine [ 204 ], hand-foot-and-mouth disease vaccine [ 205 ], cholera vaccine [ 206 ], leptospirosis vaccine, bleeding heat vaccine, and forest encephalitis vaccines. For obvious reasons, inactivated vaccines are intrinsically much safer than live vaccines, and they generally have a more complete molecular spatial structure.…”
Section: Concepts and Methods Of Vaccine Developmentmentioning
confidence: 99%